Prefrence Study of some Food Materials on the Biology of Furniture Carpet Beetle, Anthrenus flavipes LeConte (Journal of the College of Basic Education, 2022)
Furniture carpet beetle, Anthrenus flavipes LeConte is considered an important pest of animal products such as wool, hair, fur, feathers, hide and others. Its larvae feed on these materials and cause serious damage to them. While Adult beetles feed on pollen and nectar.Preference of larva and adult was investigated under laboratory conditions of 30 ± 3°c, relative humidity 50 ± 5 and photoperiodicity (hour) 1 light: 23 dark. They were fed on 8 materials, crude sheep wool, goats hair, camel hair, sheep hide, dead insects, birds feather, human hair and natural silk. Adult females raised when larvae on these materials laid total eggs on the average 45.0, 40.4, 26.2, 18.0, 26.2, 26.2, 20.0, 17.2, per female respectively.Percent hatch of these eggs was 90.00, 93.01, 86.20, 95.10, 80.31, 84.00, 68.10, 68.12 respectively Incubation period was not affected by larval food.Larval number on the average 19.8, 20.0, 8.8, 8.4, 21.8, 8.6, 4.6 and 4.2 when larvae have fed on tested materials respectively.Adult females laid total eggs on tested materials average; 18.4, 12.8,8.2, 4.6,4.2, 10.8, 2.4, and 2.8 eggs respectively. Similarly, oviposition periods were also varied. They were 9.2, 5.4, 4.2, 4.6, 5.0, 2.4, 2.0 and 1.6 days respectively. Post – oviposition periods were 5.0, 6.2, 5.0, 4.4, 8.2, 4.0, 2.2, and 2.4 days respectively.